Modelling the Relationships between Personality Factors, Perceptions of the School as a Learning Organisation and Workplace Learning of School Teachers - Tengku Faekah Tengku Ariffin; Rosna Awang Hashim; Khulida Kirana Yahya (UUM Press, 2010)
Purpose â€" In this study, a structural model based on Kurt Lewinâ€™s Field Theory was proposed to explain how the interrelationships between a person (i.e. personality factors) and his or her environment (i.e. how one perceives the school as a learning organisation) can influence the personâ€™s behaviour. The outcome behaviour of interest in this study is the teacherâ€™s engagement in workplace learning activities.   Method â€" This is a a causal-comparative study which utilizes a survey method for data collection. The sample involved a total of 400 school teachers who were selected through a multistage cluster analysis sampling procedure. The data analysis involved an adoption of the two-step procedure. The first step was the analysis of the overall measurement model, followed by the analysis of the proposed structural model through structural equation modeling (SEM).   Findings â€" Results indicated that three of five personality factors (conscientiousness, extraversion, and openness to experience) and how the teacher perceived the school as a learning organisation, are significant influences of teacherâ€™s engagement in workplace learning activities. Based on the holistic approach in model evaluation, both the overall measurement model and the structural model were found to be adequately fit.   Value â€" The study proposed a model which highlights the importance of personality factors and perceptions of the school as a learning organisation, and as significant contributors of workplace learning. Practical implications such as the improvement of personality items in the current teacher selection tool and the application of learning organisation in the school context are elaborated in this paper.